Pemberdayaan Mustahik BAZNAS Kabupaten Gresik - Ahmad Sholahuddin Alfaroby (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Poverty has always been a special concern for most countries in the world. According to the 2015 Sustainable Development Goals (SDG), poverty is a serious concern in the development of a country. This is not only a major concern for developing countries but also a threat to developed countries. A country with a high number of poor people will have several problems including family violence, premarital pregnancy, slums, and unemployment, thus hampering economic growth. This study aims to explain how the mustahik empowerment program has been able to implement Maqashid Syariah implemented by BAZNAS Gresik with subjects in accordance with this study, namely the Fakir Sepanjang Hayat program. The method used in this study is qualitative descriptive with the results of BAZNAS Gresik contributing to all aspects of the maqashid syariah indicators that have been determined by the researcher, namely in the aspects of protecting religion, protecting life, protecting reason, and maintaining property. The results of this study suggest optimizing coordination between BAZNAS and Mustahiq regarding the assistance distributed.